A low-melting-point multi-element gallium-based liquid alloy, a preparation method and application thereof
Patent Information
- Application Number
- CN202611275918.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-16
AI Technical Summary
但是,当前开发的镓基液态合金的种类较少,目前研究更多是GaIn二元合金、以及Galinstan等三元合金这些低组元合金,且较为成熟的液态金属产品也更多地聚焦在低组元合金体系中;熔点不够低(多在8℃以上);镓铟锡液体合金易氧化、性能不稳定、黏度较高、且镓基液态合金价格昂贵,限制了镓基液态合金的应用领域及工业化
[0029] (1) Based on gallium, indium and tin as the main raw materials, the present invention adds a trace amount of zinc. Under a specific ratio, the raw materials are first homogenized in a vacuum glove box and then a gallium-based liquid alloy is prepared by low-temperature melting under a specific heating and holding time. This makes the material composition uniform, diffusion complete, standard eutectic structure formed, melting point stable, melting range narrow, and the bonds between atoms weaker. This reduces the melting temperature and improves the stability of the raw material ratio, avoiding oxidation to form high-melting-point oxides. The synergistic effect of the above technical means makes the obtained liquid alloy have a melting point as low as -31.16℃, and at the same time, it does not contain bubbles, has good fluidity, good thermal conductivity, and the development process is simple.
Smart Images

Figure CN122918407A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy materials technology, specifically to a low-melting-point multi-element gallium-based liquid alloy, its preparation method, and its application. Background Technology
[0002] Mercury, commonly known as quicksilver, is a silvery-white liquid with a strong metallic luster and a density of 13.6 g / cm³. 3 Mercury is a liquid metal at room temperature, and thermometers made from its thermal expansion and contraction properties are widely used in the medical field. However, mercury is a heavy metal that is harmful to human health and causes environmental pollution.
[0003] Common liquid metallic elements include gallium (Ga), rubidium (Rb), cesium (Cs), and francium (Fr). Cesium is radioactive, and francium and rubidium are extremely unstable, limiting their application to specific fields. Gallium, besides mercury, has the lowest melting point of any metallic element (29.8℃) and a boiling point of 2403℃. It is non-toxic, non-volatile, and chemically stable. It possesses the highest electrical and thermal conductivity of any metallic element at room temperature. Furthermore, gallium maintains a wide liquid temperature range; pure gallium, even below its freezing point, can sometimes remain liquid for months, making it considered an ideal alternative to mercury as a liquid metal matrix material.
[0004] Gallium-based alloys are multi-component alloys mainly composed of Ga and other elements, which are liquid at room temperature. However, the types of gallium-based liquid alloys currently developed are relatively few. Current research focuses more on low-component alloys such as GaIn binary alloys and ternary alloys like Galinstan, and more mature liquid metal products are also concentrated in low-component alloy systems. Furthermore, their melting points are not low enough (mostly above 8°C); gallium-indium-tin liquid alloys are prone to oxidation, have unstable performance, high viscosity, and are expensive, limiting their application areas and industrialization.
[0005] Therefore, developing new multi-component alloy systems, lowering the melting point of gallium-based liquid alloys, and exploring their thermophysical properties can provide scientific basis and theoretical support for the future application and technological breakthroughs of liquid metals in thermometers and other high-performance chip heat dissipation fields, which has important practical significance and application value. Summary of the Invention
[0006] Therefore, the technical problem to be solved by this invention is to provide a low-melting-point multi-element gallium-based liquid alloy, its preparation method, and its application. The prepared gallium-based liquid alloy has a low melting point, good fluidity, stable formulation, and improved thermal conductivity compared to mercury.
[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0008] A low-melting-point multi-element gallium-based liquid alloy comprises the following components in parts by mass: 60.5-61.5 parts gallium, 22-23 parts indium, 13-14 parts tin, and 1.5-2.5 parts zinc; the liquid gallium alloy has a melting point of -31.16-10℃ and a freezing point of -9.61-1.97℃.
[0009] The aforementioned low-melting-point multi-element gallium-based liquid alloy comprises the following components in parts by mass: 60.5-61.5 parts gallium, 23 parts indium, 14 parts tin, and 1.5-2.5 parts zinc; the liquid gallium alloy has a melting point of -31.16 to 10°C and a freezing point of -9.61 to -1.97°C.
[0010] The aforementioned low-melting-point multi-gallium-based liquid alloy, wherein the multi-gallium-based liquid alloy is Ga 61.5 In 23 Sn 14 Zn 1.5 or Ga 60.5 In 23 Sn 14 Zn 2.5 .
[0011] The aforementioned low-melting-point multi-element gallium-based liquid alloy, wherein the Ga 61.5 In 23 Sn 14 Zn 1.5 Its melting point is -28.86℃ and its freezing point is -9.61℃.
[0012] The aforementioned low-melting-point multi-element gallium-based liquid alloy, wherein the Ga 60.5 In 23 Sn 14 Zn 2.5 Its melting point is -31.16℃ and its freezing point is -5.65℃.
[0013] A method for preparing a low-melting-point multi-element gallium-based liquid alloy includes the following steps:
[0014] Step A: In the glove box, weigh out 60.5-61.5 parts of gallium, 22-23 parts of indium, 13-14 parts of tin, and 1.5-2.5 parts of zinc by weight, and mix them to obtain a mixture.
[0015] Step B: The mixture is placed in a glove box within a constant-temperature magnetic stirring electric heating jacket and heated to 40-60℃ for homogenization for 0.5-1.5 hours. Then, it is heated to 100-200℃ and held for 1-2 hours to obtain a gallium-based liquid alloy. The resulting liquid gallium alloy has a melting point of -31.16-10℃ and a freezing point of -9.61-1.97℃. Homogenization ensures uniform mixing of the materials. Excessive temperature leads to severe alloying, while insufficient time results in inadequate mixing. The melting temperature after homogenization affects the alloy's microstructure and impurity content. Too low a temperature leads to component segregation and unstable melting point; too high a temperature causes oxidation, generating high-melting-point oxides and increasing the overall melting point. Holding time is a crucial factor affecting alloying; it alters the alloy's compositional uniformity, oxide impurity content, grain structure, and internal stress, ultimately changing the measured melting temperature and melting range. Short-term heat preservation can lead to incomplete diffusion, component segregation, widening of the melting range, and unstable melting point. Excessive heat preservation, on the other hand, can cause element oxidation, volatilization, imbalances in the stoichiometry, and the introduction of high-melting-point impurities, ultimately increasing the overall melting point and degrading performance. With appropriate heat preservation, the composition is homogeneous, a standard eutectic structure is formed, the melting point is stable, and the melting range is narrow.
[0016] This invention prepares gallium-based low-melting-point alloys by weighing, mixing, homogenizing, and melting all materials in a vacuum glove box, thus avoiding raw material oxidation. Furthermore, the vacuum glove box employs a constant-temperature magnetic stirring electric heating mantle for heating, ensuring uniform heating, achieving better high-temperature melting, and providing precise temperature control. The operation is simple and avoids material transfer, thereby solving the problem of easy oxidation of materials during transfer. Through appropriate equipment selection and process optimization, this invention develops a simple, stable, and low-cost preparation process.
[0017] Each raw material used in the preparation of gallium-based liquid alloys contains trace amounts of impurity elements. This invention does not perform pretreatment on any of the raw materials. Experiments revealed that chemically treating the materials before alloying to remove impurities, and comparing the properties of the alloy with that prepared from untreated raw materials, showed no significant difference in melting point, density, and wettability, but a slight increase in thermal conductivity. However, the alloy samples prepared by chemically pretreating after mixing the alloy components showed little difference in melting point and wettability, but a significant improvement in thermal conductivity. However, chemical pretreatment of the raw materials is cumbersome and cannot be performed in a vacuum atmosphere. Furthermore, the water washing process inevitably leads to re-oxidation of the raw materials, which could affect the alloy's properties. Therefore, subsequent experiments did not involve chemical pretreatment of the raw materials.
[0018] The method for preparing a low-melting-point multi-element gallium-based liquid alloy is characterized by comprising the following steps:
[0019] Step A: In the glove box, weigh out 61.5 parts gallium, 23 parts indium, 14 parts tin, and 1.5 parts zinc by weight, and mix them to obtain a mixture.
[0020] Step B: Place the mixture in a glove box within a constant-temperature magnetic stirring electric heating mantle and heat to 50°C for 1 hour to homogenize. Then heat to 100-200°C and hold for 1-2 hours to obtain Ga. 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloy; the obtained liquid gallium alloy has a melting point of -28.86~6.81℃ and a freezing point of -9.61~-1.97℃.
[0021] The preparation method of the above-mentioned low-melting-point multi-element gallium-based liquid alloy includes the following steps:
[0022] Step A: In the glove box, weigh out 61.5 parts gallium, 23 parts indium, 14 parts tin, and 1.5 parts zinc by weight, and mix them to obtain a mixture.
[0023] Step B: Place the mixture in a glove box within a constant-temperature magnetic stirring electric heating mantle and heat it to 50°C for 1 hour to homogenize. Then heat it to 150°C and hold for 1 hour to obtain Ga. 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloys; Ga 61.5 In 23 Sn 14 Zn 1.5 Liquid gallium alloy has a melting point of -28.86℃ and a freezing point of -9.61℃.
[0024] The preparation method of the above-mentioned low-melting-point multi-element gallium-based liquid alloy includes the following steps:
[0025] Step A: In the glove box, weigh out 60.5 parts gallium, 23 parts indium, 14 parts tin, and 2.5 parts zinc by weight, and mix them to obtain a mixture.
[0026] Step B: Place the mixture in a glove box within a constant-temperature magnetic stirring electric heating mantle and heat it to 50°C for 1 hour to homogenize. Then heat it to 150°C and hold for 1 hour to obtain Ga. 60.5 In 23 Sn 14 Zn 2.5 Gallium-based liquid alloys; Ga 60.5 In 23 Sn 14 Zn 2.5 Liquid gallium alloy has a melting point of -31.16℃ and a freezing point of -5.65℃.
[0027] The application of a low-melting-point multi-gallium-based liquid alloy in the preparation of a thermometer, wherein the multi-gallium-based liquid alloy used is the aforementioned low-melting-point multi-gallium-based liquid alloy or a multi-gallium-based liquid alloy prepared by the aforementioned method.
[0028] The technical solution of the present invention achieves the following beneficial technical effects:
[0029] (1) Based on gallium, indium and tin as the main raw materials, the present invention adds a trace amount of zinc. Under a specific ratio, the raw materials are first homogenized in a vacuum glove box and then a gallium-based liquid alloy is prepared by low-temperature melting under a specific heating and holding time. This makes the material composition uniform, diffusion complete, standard eutectic structure formed, melting point stable, melting range narrow, and the bonds between atoms weaker. This reduces the melting temperature and improves the stability of the raw material ratio, avoiding oxidation to form high-melting-point oxides. The synergistic effect of the above technical means makes the obtained liquid alloy have a melting point as low as -31.16℃, and at the same time, it does not contain bubbles, has good fluidity, good thermal conductivity, and the development process is simple.
[0030] (2) This invention broadens the liquid temperature range of the base liquid alloy and has good fluidity. It uses low-melting gallium-based alloy in thermometers, realizes the development of high value-added products, replaces the application of mercury in the temperature measurement field, and broadens its application in thermal management, medical and other fields. It provides scientific basis and theoretical support for the application and promotion of high-performance chip heat dissipation, and has good social benefits and application value. Attached Figure Description
[0031] Figure 1 This is a process flow diagram for preparing multi-element gallium-based liquid alloys according to the present invention;
[0032] Figure 2 Ga prepared in Example 1 61.5 In 23 Sn 14 Zn 1.5 The DSC curve;
[0033] Figure 3 Ga prepared in Example 2 61.5 In 23 Sn 14 Zn 1.5 The DSC curve;
[0034] Figure 4 Ga prepared in Example 3 61.5 In 23 Sn 14 Zn 1.5 The DSC curve;
[0035] Figure 5Ga prepared in Example 1 61.5 In 23 Sn 14 Zn 1.5 Contact angle;
[0036] Figure 6 Ga prepared in Example 2 61.5 In 23 Sn 14 Zn 1.5 Contact angle;
[0037] Figure 7 Ga prepared in Example 3 61.5 In 23 Sn 14 Zn 1.5 Contact angle;
[0038] Figure 8 Ga prepared in Example 4 61.5 In 23 Sn 14 Zn 1.5 The DSC curve;
[0039] Figure 9 Ga prepared in Example 5 61.5 In 23 Sn 14 Zn 1.5 The DSC curve;
[0040] Figure 10 Ga prepared in Example 4 61.5 In 23 Sn 14 Zn 1.5 Contact angle;
[0041] Figure 11 Ga prepared in Example 5 61.5 In 23 Sn 14 Zn 1.5 Contact angle;
[0042] Figure 12 Ga prepared in Example 6 60.5 In 23 Sn 14 Zn 2.5 The DSC curve;
[0043] Figure 13 Ga prepared in Example 7 61 In 23 S n14 Zn 2.0 The DSC curve;
[0044] Figure 14 Ga prepared in Example 8 61 In 23 S n14 Zn 1.5 Ag 0.5 The DSC curve;
[0045] Figure 15 Ga prepared in Example 9 60 In 23 S n17 The DSC curve;
[0046] Figure 16 Ga prepared in Example 6 60.5 In 23 Sn 14 Zn 2.5 Contact angle;
[0047] Figure 17 Ga prepared in Example 7 61 In 23 S n14 Zn 2.0 Contact angle;
[0048] Figure 18 Ga prepared in Example 8 61 In 23 S n14 Zn 1.5 Ag 0.5 Contact angle;
[0049] Figure 19 Ga prepared in Example 9 60 In 23 S n17 Contact angle;
[0050] Figure 20 Ga prepared in Example 1 61.5 In 23 Sn 14 Zn 1.5 The dynamic viscosity curve;
[0051] Figure 21 Ga prepared in Example 6 60.5 In 23 Sn 14 Zn 2.5 The dynamic viscosity curve;
[0052] Figure 22 Ga prepared in Example 1 61.5 In 23 Sn 14 Zn 1.5 The diffraction lines. Detailed Implementation
[0053] The materials used in the following embodiments are shown in Table 1.
[0054] Table 1 Materials used in the experiment
[0055]
[0056] The instruments used in the embodiments are shown in Table 2.
[0057] Table 2 Experimental Instruments
[0058]
[0059] The methods used for characterization and performance testing of the materials prepared in the following examples are as follows:
[0060] (1) Density test: The density of the liquid alloy is tested using the definition of density. A 1 mL syringe is used to take a sample and weigh the mass of the sample. The density of the liquid alloy is calculated. The average value is taken from 3 measurements.
[0061] (2) Melting point and solidification point test: The melting point and solidification point of the alloy were tested using a differential scanning calorimeter (DSC) (TA Q2000); the DSC test parameters are shown in Table 3 below;
[0062] Table 3 DSC Test Parameters
[0063]
[0064] (3) Composition analysis: The composition of the alloy was analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES);
[0065] (4) Flowability characterization: The kinematic viscosity of the liquid alloy samples was tested using an 1835 Ubbelohde viscometer with an inner diameter of 0.24 mm. The dynamic viscosity of the liquid alloy samples was tested using a rotational rheometer.
[0066] (5) Wettability characterization: The contact angle and surface tension of the liquid alloy were measured using a contact angle measuring instrument, the contact angle of the liquid alloy on the glass surface was measured using the protractor method, and the surface tension of the liquid alloy was measured using the pendant drop method;
[0067] (6) Testing of thermal conductivity of liquid metal: The thermal conductivity of liquid alloys was tested using the transient planar heat source method, employing a DRE-III thermal conductivity meter from Xiangtan Xiangyi Instrument Co., Ltd. Alloy samples were tested every 2 minutes, with the average value taken from three tests. The testing conditions were: room temperature, voltage 2.2V, testing time 15s, and sampling interval 20ms. The experimental parameters for thermal conductivity are shown in Table 4.
[0068] Table 4 Thermal conductivity test parameters
[0069]
[0070] (7) Structural analysis of liquid alloy: The structure of liquid alloy was analyzed using a D8 Advance X-ray diffractometer from Bruker GmbH, Germany.
[0071] Example 1
[0072] like Figure 1 As shown, a low-melting-point Ga 61.5 In 23 Sn 14 Zn 1.5 A method for preparing gallium-based liquid alloys includes the following steps:
[0073] Step A: In the glove box, weigh out 61.5g of gallium, 23g of indium, 14g of tin, and 1.5g of zinc, and mix them to obtain a mixture.
[0074] Step B: The mixture is placed in a glove box and heated to 50°C in a constant-temperature magnetic stirring electric heating mantle for 1 hour to homogenize it. Then it is heated to 150°C (alloying temperature) and held for 1 hour to obtain Ga. 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloy; the obtained liquid gallium alloy has a melting point of -28.86℃ and a freezing point of -9.61℃.
[0075] Example 2
[0076] Similarly, in the preparation of Ga 61.5 In 23 Sn 14 Zn 1.5 The gallium-based liquid alloy differs from Example 1 in that the alloying temperature is 100°C, resulting in a Ga... 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloys have a melting point of 6.9℃ and a freezing point of -1.97℃.
[0077] Example 3
[0078] Similarly, in the preparation of Ga 61.5 In 23 Sn 14 Zn 1.5 The gallium-based liquid alloy differs from Example 1 in that the alloying temperature is 200°C, resulting in a Ga... 61.5 In 23 Sn 14 Zn1.5 The melting point of gallium-based liquid alloys is 6.89℃.
[0079] The above Examples 1-3 were conducted under the following fixed experimental conditions: homogenization at 50°C for 1 hour, alloying temperatures of 100°C, 150°C, and 200°C, respectively, followed by holding at these temperatures for 1 hour to prepare Ga alloy samples. 61.5 In 23 Sn 14 Zn 1.5 The experimental results are shown in Table 5.
[0080] Table 5. Effect of alloying temperature on the properties of alloy samples
[0081]
[0082] Alloy samples Ga prepared at different temperatures (150, 100, 200℃) 61.5 In 23 Sn 14 Zn 1.5 The DCS curves are as follows: Figure 2 , 3 As shown in Figures 4 and 5, the wettability morphology is as follows: Figure 5 , 6 As shown in Figures 7 and 8.
[0083] From such Figures 2-7 And as shown in Table 5, the alloying temperature affects the Ga alloy sample. 61.5 In 23 Sn 14 Zn 1.5 The melting point and thermal conductivity are significantly affected. The alloy prepared at 150℃ has a melting point as low as -28.86℃, while the alloy sample prepared at 100℃ has better thermal conductivity, with a thermal conductivity as high as 103.53 W·m. - 1 ·K -1 The effect of alloying temperature on Ga alloy samples 61.5 In 23 Sn 14 Zn 1.5 The density and wettability are not significantly affected. Based on a comprehensive analysis of the influence of alloying temperature on alloy properties, an alloying temperature of 150℃ is recommended.
[0084] Example 4
[0085] Similarly, in the preparation of Ga 61.5 In 23 Sn 14 Zn 1.5 The gallium-based liquid alloy differs from Example 1 in that the holding time is 1.5 h, resulting in a Ga...61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloys have a melting point of 7.6℃ and a freezing point of -2.97℃.
[0086] Example 5
[0087] Similarly, in the preparation of Ga 61.5 In 23 Sn 14 Zn 1.5 The gallium-based liquid alloy differs from Example 1 in that the holding time is 2 hours, resulting in a Ga... 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloys have a melting point of 6.81℃ and a freezing point of -7.96℃.
[0088] Examples 1 and 4-5 verified that the holding time also has a significant impact on the alloy's properties. Under fixed experimental conditions: homogenization at 50℃ for 1 hour, alloying temperature 150℃, the effect of holding time on the Ga alloy sample was studied. 61.5 In 23 Sn 14 Zn 1.5 The impact on performance is shown in Table 6.
[0089] Table 6. Effect of holding time on the properties of alloy samples
[0090]
[0091] The DCS curves of the samples under different heat preservation times are shown below. Figure 2 , 8 9. The wettability morphology is as follows: Figure 5 , 10 11.
[0092] from Figure 2 , 8 As can be seen from Tables 9, 5, 10, 11 and 6, the holding time has an effect on the Ga alloy sample. 61.5 In 23 Sn 14 Zn 1.5 The melting point is significantly affected; the alloy prepared under a holding time of 1 hour has a melting point as low as -28.86℃. It also has some impact on the thermal conductivity of the samples; the alloy sample prepared under a holding time of 1.5 hours exhibits better thermal conductivity, with a thermal conductivity coefficient of 28.074 W·m. -1 ·K -1 ; For the Ga alloy sample 61.5 In23 Sn 14 Zn 1.5 The density and wettability are not significantly affected. Considering the overall effect of holding time on alloy properties, a holding time of 1 hour is recommended.
[0093] Example 6
[0094] The difference from Example 1 is that 60.5 g of gallium, 23 g of indium, 14 g of tin, and 2.5 g of zinc were weighed, while the other steps were the same, resulting in Ga... 60.5 In 23 Sn 14 Zn 2.5 Liquid gallium alloy has a melting point of -31.16℃ and a freezing point of -5.65℃.
[0095] Example 7
[0096] The difference from Example 1 is that 61g of gallium, 23g of indium, 14g of tin, and 2.0g of zinc were weighed, while the other steps were the same, resulting in Ga... 61 In 23 S n14 Zn 2.0 Gallium-based liquid alloys have a melting point of 7.50℃ and a freezing point of -6.93℃.
[0097] Example 8
[0098] The difference from Example 1 is that: 61g of gallium, 23g of indium, 14g of tin, 1.5g of zinc, and 0.5g of silver were weighed to prepare Ga 61 In 23 S n14 Zn 1.5 Ag 0.5 Gallium-based liquid alloys have a melting point of 7.47°C and a freezing point of -5.88°C.
[0099] Example 9
[0100] The difference from Example 1 is that: 60g of gallium, 23g of indium, and 17g of tin were weighed to prepare Ga 60 In 23 S n17 Gallium-based liquid alloys have a melting point of 9.85°C and a freezing point of -12.28°C.
[0101] Examples 1 and 6-9 investigated the alloy formulation, i.e., the components and proportions of each component in the alloy, which have a significant impact on the alloy's performance. If the selected proportions are inappropriate, the prepared alloy may have an excessively high melting point and be prone to segregation, failing to meet the requirements for filling thermometers. Fixed experimental conditions: raw materials were prepared without pretreatment in a vacuum glove box and homogenized at 50°C for 1 hour; other experimental conditions and results are shown in Table 7. The DCS curves of the samples from Examples 1, 6-9 are shown below. Figure 2 , 12 ~15 and wettability morphology are respectively as follows Figure 5 , 16 As shown in ~19.
[0102] Table 7. Effect of alloy formulation on alloy properties
[0103]
[0104] As shown in Table 7, Figures 2, 12-15, and Figures 5, 16-19, the composition and ratio of the alloy have a significant impact on the melting point, and also have a certain influence on the density, wettability, and thermal conductivity. The Ga prepared in Example 1... 61.5 In 23 Sn 14 Zn 1.5 The melting point is as low as -28.86℃. The Ga prepared in Example 6... 60.5 In 23 Sn 14 Zn 2.5 With a melting point as low as -31.16℃, a pentagonal alloy sample Ga was prepared by adding silver to a quaternary alloy. 61 In 23 S n14 Zn 1.5 Ag 0.5 Its melting point is 7.47℃, its wettability is similar to that of quaternary alloys, and its thermal conductivity is significantly improved compared to quaternary alloys.
[0105] The melting point and solidification point of the gallium-based liquid alloys in Examples 1 to 9 above were obtained from the data in the phase transformation curves of the measured alloys, and are summarized in Table 8 below.
[0106] Table 8 Melting and solidification points of alloy samples from Examples 1, 4-9
[0107]
[0108] As can be seen from the DSC curves of the gallium-based liquid alloys prepared in the above examples and Table 8, the melting points of the prepared alloy samples are all below 10°C. Among them, the Ga alloy prepared in Example 1... 61.5 In 23 Sn14 Zn 1.5 The melting point is as low as -28.86℃. The Ga prepared in Example 6... 60.5 In 23 Sn 14 Zn 2.5 The melting point is as low as -31.16℃. The solidification points of the prepared samples are all below 0℃, and the alloy samples have a large degree of supercooling, and can still retain the liquid phase below 0℃.
[0109] The kinematic viscosity of gallium-based alloys was measured using Ubbelohde viscometer, and the rheological properties of typical samples were tested using a rotational rheometer. To avoid oxidation-induced adhesion of the gallium alloy samples to the walls, the measurement was performed in an alkaline medium. A 5% NaOH solution was added to the alloy, and a 2:1 volume ratio of liquid metal to 5% NaOH solution was poured into a beaker. The mixture was stirred for 30 minutes in a constant-temperature magnetic stirring bath to completely remove the oxide layer on the surface of the liquid metal. Since the sample is completely immiscible with water and NaOH solution, and its density is much greater than that of water and NaOH solution, the liquid metal and NaOH solution automatically separate after stirring. The upper layer of NaOH solution acts as a liquid seal, preventing the gallium-based liquid metal from being oxidized by oxygen in the air. In this experiment, the viscosity of the alloy samples was measured using an Ubbelohde viscometer at 35℃.
[0110] Fixed experimental conditions: raw materials were not pretreated, mixed in a glove box, homogenized at 50°C for 1 hour, heated in a vacuum glove with constant temperature magnetic stirring and electric heating jacket, and other experimental conditions and alloy properties are shown in Table 9.
[0111] Table 9 Viscosities of Alloy Samples
[0112]
[0113] As can be seen from Table 9, the viscosity of the alloy samples prepared under different conditions is not significantly different, with low viscosity and good fluidity.
[0114] Sample Ga obtained in Example 1 61.5 In 23 Sn 14 Zn 1.5 Ga prepared in Example 6 60.5 In 23 Sn 14 Zn 2.5 The dynamic viscosity curve is as follows Figures 20-21 As shown. From Figures 20-21 The dynamic viscosity curves of the samples show that the Ga liquid alloy samples prepared in Examples 1 and 6, respectively... 61.5 In 23 Sn14 Zn 1.5 Ga 60.5 In 23 Sn 14 Zn 2.5 The dynamic viscosity decreases with increasing shear rate, indicating that the prepared liquid alloy is a non-Newtonian liquid and becomes thinner with increasing shear rate. (Sample Ga) 61.5 In 23 Sn 14 Zn 1.5 The shear stress increases with increasing shear rate under low shear viscosity conditions (shear rate 0.1~1), but hardly changes with shear rate under medium shear viscosity conditions (1~100); Ga sample 60.5 In 23 Sn 14 Zn 2.5 Shear stress decreases slightly with increasing shear rate under low shear viscosity conditions, and exhibits a pattern of first increasing and then decreasing under medium shear viscosity conditions (possibly due to the presence of an oxide film in the liquid alloy). Therefore, the Ga liquid alloy sample... 61.5 In 23 Sn 14 Zn 1.5 Ga 60.5 In 23 Sn 14 Zn 2.5 All of them have good liquidity.
[0115] Based on the above experimental results, the optimal experimental conditions are: no pretreatment of raw materials required; mixing in a glove box; homogenization at 50°C for 1 hour; heating at 150°C with magnetic stirring and electric heating mantle in a vacuum glove for 1 hour. A quaternary alloy formulation is suitable, with appropriate raw material ratios of: Ga 61.5%, In 23%, Sn 14%, Zn 1.5% and Ga 60.5%, In 23%, Sn 14%, Zn 2.5%. The alloy sample Ga prepared under the optimal experimental conditions... 61.5 In 23 Sn 14 Zn 1.5 (Example 1) The melting point is -28.86 ℃, Ga 60.5 In 23 Sn 14 Zn 2.5 (Example 6) has a melting point of -31.16℃ and good fluidity, which can well meet the requirements of canned thermometers.
[0116] The alloy compositions prepared in Examples 1 and 6 were analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES), and the measured compositions are shown in Table 10 below.
[0117] Table 10 Alloy Composition (Mass Fraction) / %
[0118]
[0119] As can be seen from Table 10, the measured composition of the alloy is basically consistent with the alloy formula, indicating that the alloy formula is relatively stable.
[0120] Pretreatment methods, alloy formulations, and holding times have little effect on the alloy structure, resulting in similar spectral lines. With increasing alloying temperature, the amorphous scattering peaks of the samples intensify, and the order of near-range atoms in the alloy samples increases. The Ga alloy prepared in Example 1... 61.5 In 23 Sn 14 Zn 1.5 X-ray diffraction patterns such as Figure 22 As shown, from Figure 22 It can be seen that the alloy sample prepared under suitable conditions is amorphous and has typical amorphous single-peak characteristics.
[0121] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A low-melting-point multi-element gallium-based liquid alloy, characterized in that, The composition includes the following components in parts by weight: 60.5-61.5 parts gallium, 22-23 parts indium, 13-14 parts tin, and 1.5-2.5 parts zinc; the liquid gallium alloy has a melting point of -31.16-10℃ and a freezing point of -9.61-1.97℃.
2. The low-melting-point multi-element gallium-based liquid alloy according to claim 1, characterized in that, The composition includes the following components in parts by weight: 60.5 to 61.5 parts gallium, 23 parts indium, 14 parts tin, and 1.5 to 2.5 parts zinc; the liquid gallium alloy has a melting point of -31.16 to 10°C and a freezing point of -9.61 to -1.97°C.
3. A low-melting-point multi-element gallium-based liquid alloy according to claim 1 or 2, characterized in that, The multi-gallium-based liquid alloy is Ga 61.5 In 23 Sn 14 Zn 1.5 or Ga 60.5 In 23 Sn 14 Zn 2.5 .
4. The low-melting-point multi-element gallium-based liquid alloy according to claim 3, characterized in that, The Ga 61.5 In 23 Sn 14 Zn 1.5 Its melting point is -28.86℃ and its freezing point is -9.61℃.
5. A low-melting-point multi-element gallium-based liquid alloy according to claim 3, characterized in that, The Ga 60.5 In 23 Sn 14 Zn 2.5 Its melting point is -31.16℃ and its freezing point is -5.65℃.
6. A method for preparing a low-melting-point multi-element gallium-based liquid alloy, characterized in that, Includes the following steps: Step A: In the glove box, weigh out 60.5-61.5 parts of gallium, 22-23 parts of indium, 13-14 parts of tin, and 1.5-2.5 parts of zinc by weight, and mix them to obtain a mixture. Step B: The mixture is placed in a glove box and heated in a constant temperature magnetic stirring electric heating jacket to 40~60℃ for 0.5~1.5h for homogenization, and then heated to 100~200℃ and held for 1~2h to obtain the gallium-based liquid alloy according to any one of claims 1 to 5; the obtained liquid gallium alloy has a melting point of -31.16~10℃ and a freezing point of -9.61~-1.97℃.
7. The method for preparing a low-melting-point multi-element gallium-based liquid alloy according to claim 6, characterized in that, Includes the following steps: Step A: In the glove box, weigh out 61.5 parts gallium, 23 parts indium, 14 parts tin, and 1.5 parts zinc by weight, and mix them to obtain a mixture. Step B: Place the mixture in a glove box within a constant-temperature magnetic stirring electric heating mantle and heat to 50°C for 1 hour to homogenize. Then heat to 100-200°C and hold for 1-2 hours to obtain Ga. 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloy; the obtained liquid gallium alloy has a melting point of -28.86~6.81℃ and a freezing point of -9.61~-1.97℃.
8. A method for preparing a low-melting-point multi-element gallium-based liquid alloy according to claim 6 or 7, characterized in that, Includes the following steps: Step A: In the glove box, weigh out 61.5 parts gallium, 23 parts indium, 14 parts tin, and 1.5 parts zinc by weight, and mix them to obtain a mixture. Step B: Place the mixture in a glove box within a constant-temperature magnetic stirring electric heating mantle and heat it to 50°C for 1 hour to homogenize. Then heat it to 150°C and hold for 1 hour to obtain Ga. 61.5 In 23 Sn 14 Zn 1.5 Gallium-based liquid alloys; the Ga obtained 61.5 In 23 Sn 14 Zn 1.5 Liquid gallium alloy has a melting point of -28.86℃ and a freezing point of -9.61℃.
9. The method for preparing a low-melting-point multi-element gallium-based liquid alloy according to claim 6, characterized in that, Includes the following steps: Step A: In the glove box, weigh out 60.5 parts gallium, 23 parts indium, 14 parts tin, and 2.5 parts zinc by weight, and mix them to obtain a mixture. Step B: Place the mixture in a glove box within a constant-temperature magnetic stirring electric heating mantle and heat it to 50°C for 1 hour to homogenize. Then heat it to 150°C and hold for 1 hour to obtain Ga. 60.5 In 23 Sn 14 Zn 2.5 Gallium-based liquid alloys; the Ga obtained 60.5 In 23 Sn 14 Zn 2.5 Liquid gallium alloy has a melting point of -31.16℃ and a freezing point of -5.65℃.
10. The application of a low-melting-point multi-element gallium-based liquid alloy in the fabrication of a clinical thermometer, characterized in that, The multi-gallium-based liquid alloy used is a low-melting-point multi-gallium-based liquid alloy as described in any one of claims 1 to 5, or a multi-gallium-based liquid alloy prepared by the preparation method of a low-melting-point multi-gallium-based liquid alloy as described in any one of claims 6 to 9.